Mesenchymal Stem Cells in Gastric Cancer: Vicious but Hopeful - Li, Yuyi; Zhong, Xingwei; Zhang, Yunzhu; Lu, Xinliang (Frontiers in Oncology, 2021)
Tumor progression depends on the collaborative interactions between tumor cells and the surrounding stroma. First-line therapies direct against cancer cells may not reach a satisfactory outcome, such as gastric cancer (GC), with high risk of recurrence and metastasis. Therefore, novel treatments and drugs target the effects of stroma components are to be promising alternatives. Mesenchymal stem cells (MSC) represent the decisive components of tumor stroma that are found to strongly affect GC development and progression. MSC from bone marrow or adjacent normal tissues express homing profiles in timely response to GC-related inflammation signals and anchor into tumor bulks. Then the newly recruited “naïve” MSC would achieve phenotype and functional alternations and adopt the greater tumor-supporting potential under the reprogramming of GC cells. Conversely, both new-comers and tumor-resident MSC are able to modulate the tumor biology in transcriptional dysregulation, metabolic reprogramming, and epithelial-to-mesenchymal transition, via cell-cell dependent manner or paracrine secretomes. And they also engage in remodeling the stroma better suited for tumor progression through immunosuppression, pro-angiogenesis, as well as extracellular matrix reshaping. On the account of tumor tropism, MSC could be engineered to assist earlier diagnosis of GC and deliver tumor-killing agents precisely to the tumor microenvironment. Meanwhile, intercepting and abrogating vicious signals derived from MSC are of certain significance for the combat of GC. In this review, we mainly summarize current advances concerning the reciprocal metabolic interactions between MSC and GC and their underlying therapeutic implications in the future.